If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 25 = 6w + 1 Reorder the terms: 25 + 2w = 6w + 1 Reorder the terms: 25 + 2w = 1 + 6w Solving 25 + 2w = 1 + 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. 25 + 2w + -6w = 1 + 6w + -6w Combine like terms: 2w + -6w = -4w 25 + -4w = 1 + 6w + -6w Combine like terms: 6w + -6w = 0 25 + -4w = 1 + 0 25 + -4w = 1 Add '-25' to each side of the equation. 25 + -25 + -4w = 1 + -25 Combine like terms: 25 + -25 = 0 0 + -4w = 1 + -25 -4w = 1 + -25 Combine like terms: 1 + -25 = -24 -4w = -24 Divide each side by '-4'. w = 6 Simplifying w = 6
| 5x-7+8x-55=180 | | 4x+7=47+2x | | 1/4x-7=1 | | 7(x-4)+2=51 | | f(t)=-16t^2+104t+56 | | 9s+7s= | | (6+4i)(3-7i)=0 | | -2(6y-5)= | | 6x+2xy=3+y | | 13m+4=12 | | 13-a=9 | | 4x+23+10x-1=180 | | 3x+12y+15z= | | 2ln(4)=x | | -6y=14 | | 4*2x+1=1024 | | 8-(3n-8)=9-4n | | f(x)=0.05x+30 | | b=a-14 | | -6-2x+4y=0 | | s+3.5=6 | | 3x^3+21x^2+50x+52=0 | | x/2-7x-44=0 | | 9x-73+3x+23=180 | | (x+3)(x-5)=5x-9 | | 5x/2}-x=x/6-8/3 | | 3x-2+7x+3= | | ln(x+1)+ln(x-3)=ln(3) | | g(x)=x^2-18x-8 | | 15x+7+23x-17=180 | | K-1/0 | | ln(x^4)-2ln(x)=1 |